Poetics and Politics of Borderland Dwelling: Baltis in Kargil - Radhika Gupta (South Asia Multidisciplinary Academic Journal)
The experience of ‘cross-border dwellers’ corresponds clearly neither to the category of Partition refugees nor those in exile. This article is an ethnographic case study of the Baltis in Kargil living in the India-Pakistan borderland in the province of Kashmir. It discusses the seemingly contradictory emotions of a poetics of longing for the ‘other’ side and a politics of belonging in India. I argue that a tension persists between the geobody of the nation-state and the affective body of the cross-border dweller. Further, subjective narrations and biography offer a subtle critique of the legitimating ideologies of nation-states on both sides of the ‘border’.